Proximal renal tubular acidosis in Sjögren’s syndrome: diagnostic challenge and successful management - Harshitha, K. B.; K, Supriya (International Journal of Research in Medical Sciences, 2025)
Proximal renal tubular acidosis (RTA) is a rare but important extra-glandular manifestation of Sjögren’s syndrome, often presenting diagnostic challenges due to its overlapping features with other renal and autoimmune disorders. This case report describes a 44-year-old woman with classic sicca symptoms and constitutional complaints including significant weight loss, prolonged fever, chronic cough, and oral dryness. She was found to have proteinuria, elevated creatinine, metabolic acidosis, severe hypocalcaemia, and electrocyte imbalances, markers suggestive of renal involvement. Serological work-up confirmed Sjögren’s syndrome, while detailed laboratory analysis recognized proximal (type 2) RTA accompanied by Fanconi syndrome, based on the detection of proteinuria, hypocalcaemia, hypokalaemia, and vitamin D deficiency. Differential diagnosis initially favoured plasma cell dyscrasias; however, polyclonal rather than monoclonal gammopathy, with a normal kappa-lambda ratio, established the autoimmune etiology. Hospital management included intravenous calcium gluconate, ongoing calcium and vitamin D supplementation, corticosteroids, azathioprine, sodium bicarbonate infusion, and potassium repletion, resulting in rapid symptomatic and metabolic improvement. The case highlights the complexity of distinguishing isolated proximal RTA from Fanconi syndrome and underscores the importance of early recognition and immunosuppressive management to prevent osteomalacia and progressive renal dysfunction. Regional and ethnic variability in RTA types further complicates diagnosis, confirming the need for high clinical suspicion and multidisciplinary evaluation. This report seeks to inform clinicians about the nuances of Sjögren’s-related renal disease and emphasizes individualized therapy tailored to the underlying autoimmune pathophysiology.